Could Resilience and Flourishing be Mediators in the Relationship between Mindfulness and Life Satisfaction for Saudi College Students? A Psychometric and Exploratory Study - Marei S. Younes; Mohammed R. Alzahrani (Sultan Qaboos University, 2018)
In There are few Arabic studies examining the disposition of mindfulness, resilience, and well-being of college students. The purpose of the present study is to examine the factor structure and internal consistency of the Arabic version of mindful attention awareness scale (MAAS) and the brief resilience scale, and  to test a model that describes the role of resilience and well-being, in relation to mindfulness and life satisfaction. For this reason, a study of two folds was conducted with the assistance of Umm Al-Quraa University students (n = 562; n = 534). Mindfulness, resilience, flourishing and life satisfaction scales are the variables that were used. Results show that both mindfulness and resilience scales were revealed to be unidimensional and have high reliability estimates. Both resilience and flourishing are partial mediators in the relationship between mindful and life satisfaction. In addition, resilience had an impact on flourishing. Mindfulness partially had an effect on life satisfaction. In conclusion, mindfulness and resilience scales had good structural validity and reliability.